Bacterial Spore Inactivation Technology in Solid Foods: A Review - Tian Maojin; Zhou Zheng; Hu Ying; Han Yanyan; Zhou Liang (Journal of Food Protection)
In response to physiological stress, some bacterial strains have the ability to produce spores that are able to resist conventional food heating processes and even more extreme environmental factors. Dormant spores can germinate and return to their vegetative state during food preservation, leading to food spoilage, or safety issues that pose a risk to human health. Thus, spore inactivation technology is gaining more and more attention. Several techniques have been used in liquid foods to efficiently inactivate spores, including novel thermal and nonthermal treatments. However, solid foods have unique characteristics that make it challenging to achieve the same spore inactivation effect as in previous liquid food studies. Therefore, exploring the effectiveness of spore inactivation techniques in solid foods is of great significance, and clarifying the mechanism for deactivating spore through related techniques is informative in enhancing the effectiveness of spore deactivation in solid foods. This article reviews the practical applications of spore inactivation technology in solid foods.